Design of microstrip hairpin bandpass filter for 2.9 GHz – 3.1 GHz s-band radar with defected ground structure - Ismail, Nanang; Gunawan, Teddy Surya; Kartika, Santi; Praludi, Teguh; Hamidi, Eki A. Z. (Universiti Teknologi Malaysia, 2018)
Radar has been widely used in many fields, such as telecommunication, military applications, and navigation. The filter is one of the most important parts of a radar system, in which it selects the necessary frequency and blocks others. This paper presents a novel yet simple filter design for S-band radar in the frequency range of 2.9 to 3.1 GHz. The center frequency of the filter was designed at 3 GHz with a bandwidth of 200 MHz, insertion loss larger than -3 dB and return loss less than -20 dB. Fifth order microstrip hairpin bandpass filter (BPF) was designed and implemented on Rogers 4350B substrate which has a dielectric relative constant value of (εr)= 3.48 and substrate thickness of (h) =1.524 mm. One element of the square groove was added as Defected Ground Structure (DGS) which can decrease the filter size, reduce harmonization, and increase return loss. Two scenarios were used in the measurement, i.e. with and without enclosed aluminum casing. Results showed that BPF without casing obtained the insertion loss of -1.748 dB at 2.785 GHz and return loss of -21.257 dB in the frequency range between 2.785 to 2.932 GHz. On the other hand, BPF with casing shows a better performance, in which it obtained the insertion loss of -1.643 dB at 2.921 GHz and return loss of -19.529 in the frequency range between 2.820 to 3.021 GHz. Although there is small displacement of frequency and response value between the simulation and implementation, our BPF has the ability to work on S-band radar with a frequency range of 2 to 4 GHz.